On the viscous Burgers equation in unbounded domain - Juan Limaco; Haroldo Rodrigues Clark; L. A. Medeiros (Electronic Journal of Qualitative Theory of Differential Equations, 2010)
In this paper we investigate the existence and uniqueness of global solutions, and a rate stability for the energy related with a Cauchy problem to the viscous Burgers equation in unbounded domain $\mathbb{R}×(0,∞)$. Some aspects associated with a Cauchy problem are presented in order to employ the approximations of Faedo-Galerkin in whole real line $\mathbb{R}$. This becomes possible due to the introduction of weight Sobolev spaces which allow us to use arguments of compactness in the Sobolev spaces.